2017
DOI: 10.1021/acsnano.6b07781
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Hydroxyapatite Nanohybrids for Slow Release of Nitrogen

Abstract: While slow release of chemicals has been widely applied for drug delivery, little work has been done on using this general nanotechnology-based principle for delivering nutrients to crops. In developing countries, the cost of fertilizers can be significant and is often the limiting factor for food supply. Thus, it is important to develop technologies that minimize the cost of fertilizers through efficient and targeted delivery. Urea is a rich source of nitrogen and therefore a commonly used fertilizer. We focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
248
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(285 citation statements)
references
References 19 publications
12
248
1
4
Order By: Relevance
“…Именно поэтому для фермеров и крупных компаний АПК одним из требований к используемым азотным удобрениям является пролонгированное действие веществ, сохранение влаги, регулируемая иммобилизация и доступность азота. Одним из путей решения поставленных задач является создание почвенного кондиционера, содержащего азотсодержащее органическое удобрение [4].…”
Section: Introductionunclassified
“…Именно поэтому для фермеров и крупных компаний АПК одним из требований к используемым азотным удобрениям является пролонгированное действие веществ, сохранение влаги, регулируемая иммобилизация и доступность азота. Одним из путей решения поставленных задач является создание почвенного кондиционера, содержащего азотсодержащее органическое удобрение [4].…”
Section: Introductionunclassified
“…2,3 However, compared to controlled drug release for pharmaceutics, there has been a paucity of research on the agriculture applications of nanotechnology to improve release behavior of fertilizer formulations. Previous work has reported that carbon nanotubes can enter tomato seeds, and zinc oxide nanoparticles pass into rye grass root tissues.…”
mentioning
confidence: 99%
“…9 Their method significantly reduces the amount of urea required for fertilization since it can be applied locally. Perhaps more impressively, the authors demonstrate that, with their approach, the rice crop yields are significantly enhanced even when 50% less urea is used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, more stringent regulations for reactive nitrogen emissions and discharges in developed countries have been enforced to deter air and water pollutions, which reduce the amount of reactive nitrogen to the atmosphere and water bodies. From engineering standpoint, the application of nanotechnology to agricultural plants, named phytonanotechnology (Rajan et al 2015), would be promising to reduce the amount of fertilizes applied to a cropland (Kottegoda et al 2017). Developing a wastewater treatment system to mitigate N 2 O emission and to enhance nitrogen removal by harnessing novel microorganisms could be feasible.…”
mentioning
confidence: 99%